Up to 19-year cryopreservation does not impair hematopoietic progenitor function in cord blood: a 1129-unit analysis from the largest Korean public cord blood bank - Eun Youn Roh; Hye Ryun Lee; Sue Shin; Jong Hyun Yoon; Nam-Hee Kim; Hyun-Woong Park; Byoung Jae Kim (Stem Cells Translational Medicine, 2026)
Abstract Background Whether umbilical cord blood (UCB) quality is maintained during decades of cryopreservation is critical for public banking policy. We analyzed post-thaw quality of 1129 UCB units cryopreserved for up to 19 years at Korea’s largest public cord blood bank and examined implications for shelf-life policy. Methods UCB units manually volume-reduced and cryopreserved between 2006 and 2025 underwent pre-transplant testing using their attached integral segments (median storage 6.5 years; range 16 days-19.0 years). Associations between storage duration and 19 quality indicators and 13 paired pre-/post-thaw complete blood count parameters were analyzed by Spearman correlation (ρ) before and after adjusting for era effects (processing and testing dates) to separate genuine storage effects from longitudinal analytical variation. Predictors of colony-forming unit (CFU) were ranked by univariate correlation and a Random Forest machine-learning model. Compliance with German/FACT-NetCord pre-transplant criteria was assessed. Results Associations between storage duration and quality indicators were modest before adjustment (|ρ| ≤ 0.4) and were largely abolished once differences in testing era were taken into account: the storage-duration correlations for viable CD45+ and viable CD34+ both lost significance, as did CFU/CD34 + (P = .327). The post-thaw CD34+ count was the strongest predictor of CFU. Testing date, although ranked only seventh by simple correlation, rose to second in the Random Forest model, indicating an era effect not captured by pairwise analysis. The composite pre-transplant criteria pass rate was 96.2%, remaining above 93% across all storage bins. Conclusions After up to 19 years of cryopreservation, per-CD34+ colony-forming capacity is preserved. A test-based shelf-life policy is more evidence-based than a predetermined expiration limit.